Release of a liquidity regulation: What do we learn for credit and house prices? - Bologna, Pierluigi; Cornacchia, Wanda; Galardo, Maddalena (Journal of Financial Stability, 2022)
This paper studies the effects of the release of a limit on banks’ maturity transformation – akin to the Net Stable Funding Ratio – for mortgage supply and house prices. After the regulatory easing, credit supply increased only for the banks that were previously constrained by the regulation and not for the others. We also show that the expansion in mortgages triggered by the deregulation accelerated house prices. The effect was channeled through higher demand for housing and the relaxation of borrowers’ financial constraints. Even though the impact of the credit supply shock persisted, the interaction between credit and house prices was not conducive to a housing market overheating.